2020
DOI: 10.1021/acs.energyfuels.0c02164
|View full text |Cite
|
Sign up to set email alerts
|

Speciation, Distribution, and Mobility of Hazardous Trace Elements in Coal Fly Ash: Insights from Cr, Ni, and Cu

Abstract: Coal fly ash (CFA) has gained increasing societal concerns as hazardous trace elements (HTEs) in CFA might pose environmental and public health risks. To develop better management and remediation strategies, it is highly important to obtain an in-depth understanding of the occurrence and mobility of HTEs in CFA. This study systematically characterized the speciation, distribution, and mobility of Cr, Ni, and Cu in class F and class C CFA samples using scanning electron microscopy with energydispersive X-ray sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…Cr is mainly present as Cr 3+ oxide with weak traces of Cr 6+ . Interestingly, the double peak in the XANES white line is consistent with Cr K-edge spectra of Ca 3 Cr 2 (SiO 4 ) 3 (Liu et al, 2020) suggesting a major fraction of Cr in the calcium silicate environment. The well resolved XANES features suggest a relatively ordered and highly crystalline environment.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Cr is mainly present as Cr 3+ oxide with weak traces of Cr 6+ . Interestingly, the double peak in the XANES white line is consistent with Cr K-edge spectra of Ca 3 Cr 2 (SiO 4 ) 3 (Liu et al, 2020) suggesting a major fraction of Cr in the calcium silicate environment. The well resolved XANES features suggest a relatively ordered and highly crystalline environment.…”
Section: Discussionsupporting
confidence: 68%
“…The well resolved XANES features suggest a relatively ordered and highly crystalline environment. Some amount of Cr 3+ is found in a disordered atomic environment; owing to the weakness of this contribution (around 16%) it is difficult to assess the chemical speciation: Cr acetate is a candidate but the similarity of Cr Kedge XANES in other amorphous environments like Cr 3+doped glasses or oxy-hydroxides (Ohta, 2015;Liu et al, 2020) prevents achieving a definitive answer. These results prove that the new multidetector system provides good quality XANES spectra from trace elements down to the p.p.m.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly important to analyze the occurrence, distribution and mobility of trace elements for better management and possible remediation strategy. Liu et al [37] found that low-mobility of trace elements (including Cr, Co, Cu, Ni, Zn, Cd and Pb) in class F fly ash which might be a result of particle encapsulation by glass phase. Besides certain heavy elements, coal fly ash also contains valuable rare earth elements (REE).…”
Section: Chemical and Mineralogical Composition Of Ashesmentioning
confidence: 99%
“…Class C CFA is typically derived from subbituminous and lignite coals, with 50 wt % ≤ SiO 2 + Al 2 O 3 + Fe 2 O 3 ≤ 70 wt %. These samples have been well characterized in previous studies and were labeled as samples F-1 and C-1, respectively. , The concentrations of major elements were measured using X-ray fluorescence (XRF) . The concentrations of trace metals, including REEs, were measured by inductively coupled plasma mass spectrometry (ICP-MS) after total digestion. , …”
Section: Methodsmentioning
confidence: 99%